Architecting Enterprise-Scale Data Products: A Framework for Advanced Data Science and AI/ML Operations - Seshendranath Balla Venkata, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article presents a comprehensive framework for building enterprise-scale data products that power modern Customer & Product Analytics, Data Science, artificial intelligence, and machine learning initiatives. The article examines the foundational architecture patterns, pipeline engineering strategies, and advanced distributed computing approaches in both on-prem and cloud. These are essential for developing robust data infrastructure capable of handling complex Data Analytics, Data Science, and AI/ML workflows. The article explores critical aspects of feature engineering at scale, real-time processing capabilities, and the implementation of feature stores, while addressing the challenges of data quality, governance, legal, and security in regulated environments. The article introduces a systematic approach to integrating data products with MLOps pipelines, emphasizing the importance of automated workflows, monitoring systems, and feedback loops in production environments. The findings demonstrate that successful implementation of scalable data products requires a careful balance of architectural decisions, technology selection, and operational practices. The article contributes to the field by providing actionable insights and architectural patterns that organizations can adopt to build resilient, scalable, and efficient data products for their Data Analytics, Data Science, and AI/ML use cases. This article establishes a foundational framework that bridges the gap between theoretical data architecture principles and practical implementation challenges in enterprise settings.
Keywords: Data Analytics; Data Product Engineering; Enterprise ML Infrastructure; Scalable Distributed Data Architecture; Data Governance Framework